Factors Contributing to Employee Turnover in the South African Renewable Energy Sector - Ngema, Dumsile Nondumiso (University of the Witwatersrand, Johannesburg, 2024)
The primary objective of this study was to identify the key factors drivingemployee turnover. Concurrently, the study aimed to investigate the underlyingorganisational culture disparities across different age groups and gender profiles.Additionally, it explored the impact of leadership on turnover and the relationshipbetween employee compensation and turnover. Considering the complex natureof employee turnover's impact, the development of effective retention strategieshas become a crucial need for organisations in this rapidly growing industry.Implementing these strategies is vital for retaining top talent, safeguardinginstitutional knowledge, mitigating turnover-related costs, and enhancing overallorganisational productivity. To address the study’s objectives, a digitalquantitative research survey was conducted with a sizable sample of 300employees employed in the renewable energy sector. The survey achieved a95.67% response rate, providing a robust dataset for analysis. The collected dataunderwent rigorous statistical examination, which included both inferential anddescriptive statistics. Among the key findings, organisational culture emerged asthe primary driver of employee turnover within South Africa's renewable energysector. This highlights the significance of elements such as inclusivity, employeesupport, respect, work-life balance, and ethical conduct as crucial components ofthe organisational culture. Employee compensation also played a significant rolein influencing employee turnover in this sector, with job satisfaction acting as acritical mediator in explaining the relationship between culture and employeeretention. Interestingly, the study did not identify a similar mediating role betweencompensation and turnover. Additionally, other factors such as leadership andtraining and development did not demonstrate a significant relationship withturnover. The practical implications of these findings are significant for improvinghuman resource practices in the renewable energy sector. These findings alsohighlight the importance of strengthening organisational culture while alsofocusing on job satisfaction and competitive compensation packages.Policymakers and industry associations can draw valuable insights from thefindings of this study to enhance employee retention strategies. This studycontributes meaningfully to the understanding of employee turnover in thevrenewable energy sector, not only within South Africa but with potential relevancein a broader context
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Employee turnover; Job satisfaction; Organisational culture; Organisational leadership; Training and development; Renewable energy; Retention strategies; Human resource management; UCTD; SDG-7: Affordable and clean energy